A Keystone Flap as A Reconstructive Option for Anterior Abdominal and Inguinal Defect - Mallo, Andly Resando; Oley, Mendy Hatibie (Jurnal Sehat Indonesia (JUSINDO), 2025)
The keystone flap is an effective solution to this by utilizing local tissue similar to a keystone to close the defect without the need for tissue transfer from other locations in the body. This makes it a highly effective option in reconstructing complex defects of the anterior abdomen and inguinal region, supporting complete patient recovery. This study aims to determine the effectiveness of using keystone flaps in covering large defects in the abdominal and inguinal walls after tumor removal. This study used a descriptive method with a retrospective approach. Data collection techniques in this study were literature study, observation and patient medical records. The data that has been collected is then analyzed in three stages, namely data reduction, data presentation and conclusion drawing. The results showed that the keystone flap can be used to cover extensive damage to the abdominal and inguinal walls after tumor removal with success. The keystone flap is a reasonably easy defect reconstruction, is very reliable, and has low morbidity and complications